2013
DOI: 10.1021/bm400380s
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Biopolymeric Platform for Reliable Evaluation of the Activity of pH-Responsive Amphiphile Fusogenic Peptides

Abstract: Over the past couple of decades, the sequences of several cationic and anionic pH-responsive amphiphile fusogenic peptides (FPs) have been reported in the literature. Due to their endosome membrane disrupting activity, these peptides have been routinely used for enhancing the efficacy of drug/gene delivery systems. However, no accurate comparative study has been performed to establish the precise correlation between FP sequence and its impact on enhancing drug/gene delivery efficiency. Therefore, there has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…Hatefi's group have created numerous multifunctional nonviral delivery systems with discrete interchangeable motifs, each one of which is designed to overcome a specific biological barrier [10,11]. While such systems are excellent examples of what can be achieved, the large-scale production of such recombinant proteins can be time-consuming and therefore peptide-mediated gene delivery presents a highly attractive option.…”
Section: Introductionmentioning
confidence: 99%
“…Hatefi's group have created numerous multifunctional nonviral delivery systems with discrete interchangeable motifs, each one of which is designed to overcome a specific biological barrier [10,11]. While such systems are excellent examples of what can be achieved, the large-scale production of such recombinant proteins can be time-consuming and therefore peptide-mediated gene delivery presents a highly attractive option.…”
Section: Introductionmentioning
confidence: 99%
“…Whether GALA should be labeled as fusogenic peptide or cell penetrating peptide remained in disputation, however, its marvelous drug delivery capacity should never be ignored; GALA and GALA-related peptide (such as cationic KALA and RALA, etc.) could escape endosome entrapment and improve gene transfection [120][121][122][123][124][125].Harashima et al…”
Section: Gala-related Peptides (Such As Kala) Was Inspired By Influenmentioning
confidence: 99%
“…It was worth noticing that the penetrating and fusion property was concealed until these peptides reached acidic environment such as endosomes, minimizing its cytotoxicity to normal tissues. Among them, GALA peptide should be counted as the most classic one since it showed high endosomal activity and low cytotoxicity [125]. Recently, Harashima et al discovered that GALA peptide could recognize the sialic acid-terminated sugar chains on pulmonary endothelium, which could aid in the cellular uptake of GALA-functionalized MEND by lung endothelial cells, and the nucleic acid delivery could be further improved by the endosomal membrane fusion by GALA peptide [126].…”
Section: Gala-related Peptides (Such As Kala) Was Inspired By Influenmentioning
confidence: 99%
“…Although improving the efficiency of endosomal escape by CPPs alone is difficult, the ability to facilitate endosomal escape has been discovered in fusogenic peptides (FPs), and some studies have utilized FPs for intracellular delivery [3,[15][16][17]. For example, Wadia et al combined the TAT peptide and fusogenic HA2 peptide derived from hemagglutinin from influenza virus and demonstrated that dTAT-HA2 efficiently promoted the escape from macropinosomes [16].…”
Section: Introductionmentioning
confidence: 99%
“…FPs have membrane-disrupting activities under acidic conditions, through pH-dependent conformational changes [18], and consequently, they are expected to facilitate endosomal escape at acidic pH. The pH-dependence of FPs is an important characteristic for their application in drug delivery systems (DDS) with cell targeting because it reduces non-specific effects [15]. However, the FPs studied so far are not adequately efficient in facilitating endosomal escape; thus, novel FPs with higher activity are required.…”
Section: Introductionmentioning
confidence: 99%